Bioequivalence Study of Two Oral Methocarbamol Formulations in Healthy Subjects Under Fasting Conditions: A Randomized, Open-Label, Crossover Clinical Trial - Ana Ascaso-del-Rio; Paola Camargo-Mamani; Inmaculada Gilaberte; Mónica Díez-Hochleitner; Leonor Laredo-Velasco; Teresa Iglesias-Hernangómez; María Rosario Salas-Butrón; Laura Galán Caballero; Iván Alejandro Díaz-Rengifo; Carla Pérez-Ingidua; Emilio Vargas-Castrillón; Antonio Portolés-Pérez (Pharmaceuticals)
Objective: This study aimed to assess the bioequivalence of two oral methocarbamol formulations, as follows: the test (T) methocarbamol 1500 mg tablets and the reference (R) Robaxin® 500 mg tablets (3 tablets, total dose: 1500 mg) under fasting conditions, and compare their pharmacokinetic performance. Methods: This was a single-center, phase I, randomized, open-label (blinded for analytical determination), two-sequence, two-period, crossover, bioequivalence study. A total of 32 healthy volunteers were randomly assigned to receive the T-R or R-T administration sequence. Each volunteer received a single dose of each methocarbamol formulation (T or R) separated by a washout period of 7 days. To evaluate the pharmacokinetic profile, blood samples were collected at nineteen time points after dosing. Results: The arithmetic mean Cmax was 31.72 µg/mL for R and 32.39 µg/mL for T, and the arithmetic mean AUC0−t was 90.25 h × µg/mL and 89.72 h × µg/mL, respectively. All adverse events reported were mild for both formulations. The 90% confidence intervals for the corresponding logarithmically transformed geometric mean ratios of Cmax and AUC0−t fell within the acceptance interval of 80.00–125.00%, as their values were 91.67–112.47% for ln(Cmax) and 92.34–103.47% for ln(AUC0−t). Conclusion: Therefore, one tablet of methocarbamol 1500 mg was found to be bioequivalent to the Robaxin® 500 mg tablets (3 tablets), with comparable tolerability and safety profiles.